2017
DOI: 10.1142/s021945541750064x
|View full text |Cite
|
Sign up to set email alerts
|

Buckling and Free Vibration of Nonuniformly Heated Functionally Graded Carbon Nanotube Reinforced Polymer Composite Plate

Abstract: Buckling and free vibration behavior of functionally graded carbon nanotube reinforced polymer composite plate subjected to nonuniform temperature fields have been investigated using finite element approach. The effective material constants of the plate are obtained using the extended rule of mixture along with efficiency parameters of the carbon nanotube (to include geometry-dependent material properties). Influence of boundary conditions, aspect ratio, functional grading of the carbon nanotube, nonuniform th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The experimental set up is shown in Figure- The critical load of buckling is determined from the load-displacement curve as shown in Figure-6. Where the point that left from the straight line is determined from the graphics and the corresponding vertical coordinate represents the critical load of buckling [11]. The sample models are then meshed.…”
Section: Buckling Testmentioning
confidence: 99%
“…The experimental set up is shown in Figure- The critical load of buckling is determined from the load-displacement curve as shown in Figure-6. Where the point that left from the straight line is determined from the graphics and the corresponding vertical coordinate represents the critical load of buckling [11]. The sample models are then meshed.…”
Section: Buckling Testmentioning
confidence: 99%
“…The results revealed that the nonuniformly heated beam critical temperature is totally different from uniformly heated beam and also concluded that the critical temperature of the beam significantly varies with the position of the heating source. George et al 15 analysed the functionally graded carbon nanotube reinforced polymer composite nonuniformly heated plate buckling and free vibration with the help of finite element method. The study showed that the type of CNT reinforcement and variation in temperature field are the two factors which produce a significant impact on buckling strength of the polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…George et al. 15 analysed the functionally graded carbon nanotube reinforced polymer composite nonuniformly heated plate buckling and free vibration with the help of finite element method. The study showed that the type of CNT reinforcement and variation in temperature field are the two factors which produce a significant impact on buckling strength of the polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…Ansari et al 12 examined the buckling and free vibration behavior of CNTRC annular sector plates in thermal environments using the generalized differential quadrature method (GDQM). George et al 13 investigated the buckling and free vibration response of CNT polymer plates subjected to nonuniform temperature fields using finite element approach. Phung-Van et al 14 used isogeometric analysis and generalized higher-order shear deformation theory (HSDT) to consider the influence of size dependency of FG-CNTRC nanoplates.…”
Section: Introductionmentioning
confidence: 99%